Effects of Ginseng on Neurological Disorders - Hou, Wei; Wang, Yingping; Zheng, Peihe; Cui, Ranji (Frontiers in Cellular Neuroscience, 2020)
Ginseng (Panax ginseng Meyer), a famous traditional medicinal herb, has been widely used for many centuries. Numerous studies have shown that ginseng has a positive effect on the prevention and treatment of neurological disorders. In this review, we summarized the effects of ginseng in treating neurological diseases, particularly the anti-depressant effects of ginseng. Furthermore, its potential mechanism was also outlined. Therefore, this review may provide new insight into the treatment of ginseng on neurological diseases.